Atlantic History and the teaching of history (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2019)
The dossier presented here is the result of the collective work of the American History I, General History IV and Didactic planning and teaching practices in history of the Faculty of Humanities and Educational Sciences of the National University of La Plata, in the teaching workshop that took place in the framework of the First International Conference on the History of the Atlantic World in Early Modernity c.1500-1800 in October 2018 and was attended by researchers, teachers and students. The aforementioned workshop was intended to deepen the link between the contributions and questions that went through the discussion in the different commissions and its impact on the teaching of history. As we set out, we synthesize the conclusions that were discussed in the aforementioned workshop, realizing a highly enriching collective work space for all its participants.
Keywords: history of the Atlantic World; teaching; research